An electrochemical measurement method for the lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes

By establishing a linear standard curve of the capacity change ratio and mixing rate of the standard sample of ternary positive electrode material, the problems of high cost and insufficient throughput of lithium nickel mixed displacement in the prior art are solved, and low-cost and high-pass are achieved The test method of quantity improves the accuracy of the test results.

CN115436442BActive Publication Date: 2025-02-18XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211138752.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-19
Publication Date
2025-02-18
Estimated Expiration
2042-09-19

AI Technical Summary

Technical Problem

The prior art cannot achieve low-cost and high-throughput testing lithium-nickel mixed displacement rate, resulting in high testing costs and insufficient throughput.

Method used

By measuring the capacity change ratio of the standard sample of the ternary positive electrode material and establishing a linear standard curve with the mixing rate, the lithium nickel mixing rate of the sample to be tested is then measured.

Benefits of technology

The lithium-nickel mixing rate of high-throughput testing of ternary positive electrode materials on lithium battery electrode sheets is achieved, reducing testing costs, simplifying operations, and improving the accuracy of test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115436442B_ABST
    Figure CN115436442B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemical measurement technology and discloses an electrochemical measurement method for the lithium-nickel mixed rate of a ternary positive electrode material in a lithium battery electrode. The principle of the method is based on the capacity change ratio q of the ternary positive electrode material in the lithium battery electrode in the discharge stage in the potential range of 4.30V to 3.80V and the potential range of 4.30V to 2.80V. re2 / q re1 And lithium nickel mixing rate x Ni The present invention determines the capacity change ratio of a set of ternary positive electrode material standard samples #imgabs0# and establishes its relationship with the mixing rate x Ni,0‑n The linear standard curve between the two is used to simultaneously determine the capacity change ratio of the ternary positive electrode material sample to be tested#imgabs1#Calculate the lithium-nickel mixing rate x of the ternary positive electrode material sample to be tested based on the linear standard curve Ni,1‑n Compared with the conventional XRD test method, it has the advantages of simple equipment, convenient operation, convenient experimental data processing and high-throughput testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical measurement, and in particular relates to an electrochemical measurement method for the lithium-nickel mixing rate of a ternary positive electrode material in a lithium battery electrode. Background Art

[0002] Lithium nickel cobalt manganese (NCM) ternary cathode materials have been widely used in power lithium batteries with the promotion of new energy vehicles. Ternary cathode materials have the advantages of high energy density, good cycle performance and long cycle life, and have become one of the mainstream cathode materials for power batteries. The performance of power lithium batteries depends on the maximum performance of raw materials through specific manufacturing processes, among which the performance of cathode materials plays a key role. During the sintering process of ternary cathode materials, due to Li + and Ni 2+ The ionic radius of the ternary positive electrode materials is similar, and they will occupy each other's positions, which is very easy to produce lithium-nickel mixing. Since the mixing is disordered, it is an important reason for the poor electrochemical performance and cycle stability of the battery. Therefore, in the process of research and development and production, quantifying and evaluating the lithium-nickel mixing rate of the ternary positive electrode materials is of great significance for controlling the quality of positive electrode materials, analyzing abnormal materials, and developing new materials.

[0003] The conventional detection method for the lithium-nickel mixing rate of ternary positive electrode materials is to achieve it through X-ray diffraction (XRD) analysis, and the ratio of the diffraction peak intensity of the (003) plane and the diffraction peak intensity of the (104) plane in the XRD diffraction spectrum R = I (003) / I (104) is used to measure the degree of ion mixing. The R value method can quickly and qualitatively describe the degree of ion mixing. However, since the ternary positive electrode material is a layered structure, the intensity of the (003) peak will be affected by the preferred orientation and cause misjudgment. Furthermore, the parameters of the lithium-nickel mixing rate can be obtained by full spectrum fitting of high-quality X-ray diffraction patterns. This method is based on the Rietveld full spectrum fitting principle, that is, based on the assumption of crystal structure model and structural parameters, combined with a specific peak shape function to calculate the polycrystalline diffraction spectrum. The lithium-nickel mixing rate is mainly quantitatively analyzed by fitting the occupancy rate. However, the Rietveld full spectrum fitting requires the adjustment of scaling factors, background functions, lattice constants, peak shape parameters, atomic coordinates, temperature factors, transparency and other parameters, which is cumbersome to operate and cannot achieve high-throughput testing. At the same time, XRD equipment is expensive and the testing cost is high. Summary of the invention

[0004] The purpose of the present invention is to overcome the technical problem that low-cost and high-throughput testing of lithium-nickel mixing rate cannot be achieved in the prior art, and to provide an electrochemical measurement method for the lithium-nickel mixing rate of a ternary positive electrode material in a lithium battery electrode. The measurement method makes up for the high test cost and insufficient throughput of calculating the lithium-nickel mixing rate using the XRD method, and has a very large promoting effect on the low-cost and high-throughput measurement of ternary positive electrode materials and the product development, failure analysis and online evaluation of ternary positive electrode materials in lithium battery electrodes under working conditions.

[0005] The existing methods for measuring the lithium-nickel mixing rate in ternary positive electrode materials are all measured and analyzed by XRD method, which cannot meet the high-throughput requirements of existing product development. The inventors of this application have found through in-depth and extensive research that the lithium-nickel mixing rate of ternary positive electrode materials on pole pieces between different lithium batteries has a linear relationship with the ratio of the capacity change between a specific steady-state starting potential and a specific steady-state ending potential during discharge. Among them, the steady-state starting potential refers to the open circuit potential when the lithium battery is in a stable equilibrium state. Based on this further research, the present invention is completed.

[0006] Specifically, the present invention provides an electrochemical measurement method for the lithium-nickel mixing rate of a ternary positive electrode material in a lithium battery electrode, wherein the method comprises selecting at least three ternary positive electrode material standard samples with known lithium-nickel mixing rates, wherein the main components in the ternary positive electrode material standard samples are the same as the main components in the ternary positive electrode material to be tested samples, the ternary positive electrode material standard samples are made into reference electrodes by the same process as the lithium battery electrode, the reference electrode and the lithium battery electrode are assembled into a battery by the same method, and then the formation and specific capacity tests are performed under the same conditions, and the capacity change q in the potential range of 4.30V to 3.80V in each battery discharge stage is measured. re1 And the capacity change q in the potential range of 4.30V to 2.80V re2 , the lithium-nickel mixing rate x of the standard sample of the ternary cathode material Ni As the ordinate, its capacity change ratio q re2 / q re1 A linear standard curve is established as the horizontal axis, and the lithium-nickel mixing rate of the ternary positive electrode material to be tested in the lithium battery electrode is obtained on the linear standard curve according to the ratio of its capacity change.

[0007] In a preferred embodiment, the method comprises the following steps:

[0008] S1: Select at least three lithium-nickel mixing ratios with known values ​​of x Ni,0-n Ternary cathode material standard sample M 0-n, a reference electrode is made by the same process as the lithium battery electrode, and the reference electrode and the lithium battery electrode are assembled into a battery by the same method to obtain a reference battery C 0-n and the battery under test C 1-n ;

[0009] S2: The reference battery C obtained in step S1 0-n and the battery under test C 1-n Carry out formation and specific capacity tests under the same conditions and record the reference battery C 0-n The capacity change in the discharge phase when the steady-state potential is between 4.30V and 3.80V And the capacity change in the potential range of 4.30V to 2.80V And calculate the capacity change ratio At the same time, record the battery C 1-n The capacity change in the discharge phase when the steady-state potential is between 4.30V and 3.80V And the capacity change in the potential range of 4.30V to 2.80V And calculate the capacity change ratio

[0010] S3: Using ternary cathode material reference sample M 0-n The mixing rate x Ni,0-n As the ordinate, the capacity change ratio As the abscissa, a linear standard curve was established;

[0011] S4: Calculate the ternary positive electrode material sample M to be tested according to step S2 1-n Capacity change ratio The ternary cathode material sample M to be tested is calculated according to the linear standard curve in step S3. 1-n The lithium nickel mixing rate x Ni,1-n .

[0012] In a preferred embodiment, the number of the standard samples of the ternary positive electrode materials is 4 to 6.

[0013] In a preferred embodiment, the ternary positive electrode material is a lithium-nickel-cobalt-manganese ternary positive electrode material.

[0014] In a preferred embodiment, the lithium-nickel mixing ratio of the standard sample of the ternary positive electrode material is measured by an X-ray diffraction full spectrum fitting method.

[0015] In a preferred embodiment, the specific capacity test is completed in the battery discharge stage, and the potential range of the capacity change is determined by setting the steady-state starting potential and the steady-state ending potential; taking the lithium metal electrode potential as the reference zero potential, the steady-state starting potential is 4.30V vs Li, the steady-state ending potentials are 3.80V vs Li and 2.80V vs Li, respectively, and the steady-state potential ranges are 4.30V~3.80V vs Li and 4.30V~2.80V vs Li, respectively.

[0016] In a preferred embodiment, the control of the steady-state starting potential and / or the steady-state ending potential in the discharge stage is achieved by combining a constant current discharge CC step and a constant voltage discharge CV step.

[0017] In a preferred embodiment, the current size of the constant current discharge CC step is measured by a multiplier, and the multiplier is 0. <C≤1.0。

[0018] In a preferred embodiment, the ratio is 0 <C≤0.5。

[0019] In a preferred embodiment, the termination condition of the constant current discharge CC step is the steady-state starting potential or steady-state ending potential measured by electrochemical measurement.

[0020] In a preferred embodiment, the potential of the constant voltage discharge CV step is set to a steady-state starting potential or a steady-state ending potential.

[0021] In a preferred embodiment, the duration of the constant voltage discharge CV step is 10 min. <t≤180min。

[0022] In a preferred embodiment, the duration of the constant voltage discharge CV step is 60 min≤t≤180 min.

[0023] The present invention has the following beneficial effects:

[0024] (1) The present invention innovatively proposes an electrochemical measurement method for the lithium-nickel mixing rate of a ternary positive electrode material in a lithium battery electrode. The principle of the method is based on the capacity change ratio q of the ternary positive electrode material in the lithium battery electrode in the two specific potential intervals of 4.30V to 3.80V and 4.30V to 2.80V during the discharge stage. re2 / q re1 And lithium nickel mixing rate x Ni The present invention measures the capacity change ratio of a set of ternary positive electrode material standard samples. And establish its relationship with the mixing rate x Ni,0-nThe linear standard curve is used to determine the capacity change ratio of the ternary cathode material sample to be tested. Calculate the lithium-nickel mixing rate x of the ternary positive electrode material sample to be tested according to the linear standard curve Ni,1-n The electrochemical measurement method of the lithium-nickel mixing ratio of the ternary positive electrode material in the lithium battery electrode provided by the present invention can realize the testing of the lithium-nickel mixing ratio of the ternary positive electrode material on the lithium battery electrode sheet. Compared with the conventional XRD test method, it has the advantages of simple equipment, convenient operation, convenient experimental data processing and high-throughput testing.

[0025] (2) The present invention can reduce the relative error of the test by optimizing the steady-state starting potential and the steady-state ending potential and controlling the CC step and CV step conditions, thereby further improving the accuracy and precision of the test results. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the lithium-nickel mixing ratio x of the standard sample of the ternary positive electrode material in Example 1 Ni and capacity change ratio q re2 / q re1 Linear standard curve graph.

[0027] Figure 2 is the lithium-nickel mixing ratio x of the standard sample of the ternary positive electrode material in Example 3 Ni and capacity change ratio q re2 / q re1 Linear standard curve graph. DETAILED DESCRIPTION

[0028] The following are definitions of some terms used in the present invention. Other terms not mentioned here have definitions and meanings well known in the art and are not described here one by one.

[0029] In the present invention, a two-electrode electrolytic cell system can be selected for the specific capacity test, wherein the two-electrode electrolytic cell system is commonly a button cell, and the two-electrode electrolytic cell system used in the present invention is a button cell. The battery shell can be a commercially available battery shell, such as any model such as CR2023, CR2025 and CR2016, and the battery shell used in the present invention is preferably CR2023. The method for making a two-electrode electrolytic cell system (button cell) comprises the following steps:

[0030] Step 1: The positive electrode sheet uses aluminum foil as the current collector, and the positive electrode material of the lithium battery is a ternary positive electrode material (the ternary positive electrode material used in the present invention is preferably a lithium nickel cobalt manganese ternary positive electrode material), and its mass percentage is controlled at ≤96.4%. Commonly used conductive agents can be carbon-based conductive agents, and specific examples thereof include but are not limited to: at least one commercially available conductive material of acetylene black (AB), conductive carbon black and Super P. The conductive agent used in the present invention is preferably Super P, and its mass percentage is controlled at ≥1.5%. The binder system preferably uses a polyvinylidene fluoride (PVDF) system, and its mass percentage is controlled at ≥2.1%.

[0031] The lithium nickel cobalt manganese ternary positive electrode material, the conductive agent, the binder system and N-methyl pyrrolidone are mixed and stirred together and slurried in a degassing machine to form a slurry, and the viscosity of the slurry is controlled to be 7000-9000mPa·s, for example, 7000mPa·s, 7500mPa·s, 8000mPa·s, 8500mPa·s, 9000mPa·s and any value therebetween. Preferably, the slurry is evenly coated on an aluminum foil using an automatic coating machine to form an original electrode sheet, and the original electrode sheet is placed in a vacuum oven and dried at 120°C for 4 hours, and then placed in a blast oven and dried at 80°C for 12 hours. Preferably, the linear speed of the roller press is set to 2.0 m / min, and the rolling pressure is set to 1.3 MPa as the starting value. After the pressure stabilizes, the above-mentioned electrode sheet is placed for rolling. The thickness of the test sheet during the rolling process is detected with a micrometer. The thickness at three different positions is taken. When the difference between any two positions is no more than 3 microns and the average thickness L is 50±3 microns, the rolling is stopped to obtain the test sheet.

[0032] Step 2: Use a punching die with a diameter of 14 mm to cut out several small electrode sheets at different positions of the above test piece, select small electrode sheets with regular morphology, flat surface and edges, and weigh them with a 1 / 10,000 balance, put the weighed small electrode sheets into a vacuum drying oven and evacuate to 0.1 MPa, and store them for later use.

[0033] Step 3: Assemble button cells in an inert gas glove box where the mass content of water and oxygen is less than or equal to 0.0005%. The battery specification is CR2023, the diaphragm is a polypropylene film, and the negative electrode is a lithium sheet. The electrolyte preferably uses a mixed solvent of organic carbonates, and specific examples include but are not limited to: cyclic carbonates of ethylene carbonate (EC) and propylene carbonate (PC) and mixed solvents of chain carbonates of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC). More preferably, the electrolyte solvent of the present invention uses a mixed solvent with a volume ratio of EC / DEC of 1:1. The conductive salt in the electrolyte of the present invention preferably uses 1M lithium hexafluorophosphate. Preferably, a cosolvent such as ethyl acetate (EA) and / or methyl butyrate (MB) can be added to the electrolyte as needed; and a functional additive can be added as needed, such as a functional additive of at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), lithium borate (Li-BOB), borate (BC), cycloboroxine, biphenyl and its derivatives, and 4-ethyldicyclohexyl ketone. The sealing machine is used for sealing, and the packaging pressure of the button cell is preferably 800 Pa, and the packaging time is preferably 5 seconds.

[0034] In the present invention, a group of known lithium-nickel mixing ratios x is selected. Ni,0-n Ternary cathode material standard sample M 0-n The ternary cathode material standard sample M 0-n The number of the selected ternary positive electrode material standard samples M is at least three, preferably 4 to 6. 0-n The main components in the standard sample of the ternary positive electrode material are the same as the main components in the sample of the ternary positive electrode material to be tested. The term "same main components" means that the contents of nickel, cobalt and manganese are consistent. 0-n The lithium-nickel mixing ratio is preferably measured by an X-ray diffraction (XRD) full spectrum fitting method. 0-n And the ternary cathode material sample M 1-n Electrode sheets were prepared according to the same process conditions as above and assembled into button cells, which were marked as reference cells C and C respectively. 0-n and the battery under test C 1-n . Reference battery C 0-n and the battery under test C 1-nAfter sealing, formation and specific capacity tests are respectively carried out on a lithium battery electrical performance tester; preferably, in the same steady-state potential range during the discharge stage, with the lithium metal electrode potential as the reference zero potential, the steady-state starting potential is 4.30 V vs Li, and the steady-state ending potentials are 3.80 V vs Li and 2.80 V vs Li respectively. That is, the steady-state potential ranges of the capacity change amount during the discharge stage are 4.30 V - 3.80 V vs Li and 4.30 V - 2.80 V vs Li respectively. That is, at the same steady-state starting potential and the same steady-state ending potential, record the reference battery C 0-n and the battery under test C 1-n 's capacity change amount, and calculate the ratio, which are respectively recorded as and The unit "V vs Li" refers to the potential corresponding to the lithium metal electrode potential as the reference zero potential.

[0035] In the electrochemical measurement of the present invention, the control of the steady-state starting potential and / or the steady-state ending potential during the discharge stage can be achieved by combining a constant current discharge (CC) step and a constant voltage discharge (CV) step. Preferably, the current magnitude of the CC step is measured by a rate, that is, the multiple of the current corresponding to the discharge capacity in 1 hour is measured. The rate can be 0 < C ≤ 1.0, such as 0.01C, 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, 0.6C, 0.7C, 0.8C, 0.9C, 1.0C and any value between them. Further, the rate of the CC step can be 0 < C ≤ 0.5, such as 0.01C, 0.1C, 0.2C, 0.3C, 0.4C, 0.5C and any value between them. The termination condition of the CC step is the steady-state starting potential or the steady-state ending potential of the electrochemical measurement. In the electrochemical measurement of the present invention, during the discharge stage, the CV step is implemented immediately after the CC step, where the potential is set to the steady-state starting potential or the steady-state ending potential. The duration of the CV step can be 10 min < t ≤ 180 min, such as 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min and any value between them. Further, the duration of the CV step can be 60 min ≤ t ≤ 180 min, such as 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min and any value between them.

[0036] In the present invention, the lithium-nickel mixing rate x of a set of standard samples of ternary positive electrode materials is Ni,0-n (That is, x Ni ) and capacity change ratio (That is, q re2 / q re1 ) can be expressed by formula (1):

[0037]

[0038] In formula (1),

[0039] x Ni,0-n —Li-nickel mixing ratio of standard sample of ternary cathode material;

[0040] —Capacity change in the potential range of 4.30V to 3.80V during discharge of the standard sample of ternary cathode material;

[0041] —Capacity change in the potential range of 4.30V to 2.80V during discharge of the standard sample of ternary cathode material;

[0042] A—intercept coefficient of the linear standard curve;

[0043] B—slope coefficient of the linear standard curve.

[0044] According to the above ternary cathode material standard sample M 0-n The linear standard curve of the ternary cathode material sample M was measured under the same conditions. 1-n Capacity change ratio Then, it is substituted into formula (1) to directly calculate the ternary cathode material sample M 1-n The lithium nickel mixing rate x Ni,1-n .

[0045] The method for evaluating the lithium-nickel mixed rate of the ternary positive electrode material in the lithium battery electrode provided by the present invention has the main improvement of estimating the lithium-nickel mixed rate of the ternary positive electrode material in the battery according to the test results of the battery specific capacity. As for other aspects, such as how the active material is made into an electrode, how the electrode is assembled into a battery, the battery formation method, charging and discharging method, how to measure the specific capacity during the charging and discharging process, etc., they can be the same as the prior art, which is known to those skilled in the art and will not be elaborated here.

[0046] Embodiments of the present invention will be described in more detail below. Although embodiments of the present invention are described below, it should be understood that the present invention can be realized in various forms and should not be limited by the embodiments set forth herein. In the embodiment, specific techniques or conditions not indicated are carried out according to the techniques or conditions described in the document in this area or according to the product specification. The reagents or instruments used are not indicated by the manufacturer, and are conventional products that can be obtained commercially.

[0047] Example 1

[0048] Four commercially available ternary cathode materials with known lithium-nickel mixing ratios (measured by XRD full spectrum fitting method) were selected as standard samples. The contents of nickel, cobalt and manganese in these four standard samples were 70wt%, 15wt% and 15wt%, respectively, and were marked as M, M and M. 0-1 、M 0-2 、M 0-3 、M 0-4 . The above standard samples, conductive agent Super P and binder PVDF were mixed and slurried in a mass ratio of 9:0.14:0.2, and electrode test pieces were made using general process conditions and assembled into button batteries. The button battery specification is CR2023, the positive electrode is the selected ternary positive electrode material, the negative electrode is a lithium sheet, the separator is a polypropylene film, the electrolyte solvent is a EC / DEC mixed solvent with a volume ratio of 1:1, and the conductive salt is 1M lithium hexafluorophosphate. The packaging pressure of the button battery is 800Pa, and the packaging time is 5 seconds. The reference batteries made from the above ternary positive electrode material standard samples are marked as C 0-1 , C 0-2 , C 0-3 , C 0-4 , a total of 4 sets of tests were carried out.

[0049] The reference battery C 0-1 , C 0-2 , C 0-3 , C 0-4 The necessary formation and specific capacity tests were performed respectively, and then the battery was pre-charged to a state of charge (SOC) of 100%, at which point the steady-state voltage was controlled at 4.30V vs Li. On a lithium battery electrical performance tester with a potential accuracy of 0.3mV, the discharge phase was measured by combining a constant current discharge CC step with a constant voltage discharge CV step. First, the capacity change in the 4.30V to 3.80V vs Li range was measured. Then continue to discharge to 2.80V vs Li, and record the capacity change in the range of 4.30V to 2.80V vs Li. The discharge current of the constant current discharge CC step is marked with a multiple, which is set to 0.1C, and the duration of the constant voltage discharge CV step is set to 1 hour.

[0050] According to the lithium-nickel mixing rate x of the standard sample of the ternary positive electrode material Ni,0-n And the capacity change ratio of the two potential intervals of 4.30V~3.80V vs Li and 4.30V~2.80V vs Li Draw a linear standard curve. The test results are shown in Table 1. The linear standard curve is shown in Figure 1 As shown:

[0051] Table 1 Test results of lithium-nickel mixing rate and capacity variation of standard samples of ternary positive electrode materials in Example 1

[0052]

[0053] Example 2

[0054] A commercially available ternary positive electrode material with an unknown lithium-nickel mixing ratio is selected as the ternary positive electrode material to be tested sample M 1-1 , wherein the contents of nickel, cobalt and manganese are 70wt%, 15wt% and 15wt% respectively, and the battery C to be tested is prepared using the same slurry composition and the same process conditions as in Example 1. 1-1 , and at the same time make parallel test sample battery C 1-2 , C 1-3 , C 1-4 . Place the battery C 1-1 , C 1-2 , C 1-3 , C 1-4 The necessary formation and specific capacity tests were performed respectively, and then the battery was pre-charged to a state of charge (SOC) of 100%, at which time the steady-state voltage was controlled at 4.30 V vs Li. Then, in the discharge stage, the same electrical performance tester and the same test conditions as in Example 1 were used to record the capacity change in the range of 4.30 V to 3.80 V vs Li and 4.30 V to 2.80 V vs Li. and According to the capacity change ratio of the ternary cathode material to be tested in the two potential ranges of 4.30V~3.80V vs Li and 4.30V~2.80V vsLi during the discharge stage Read the lithium-nickel mixing rate x in the standard curve of Example 1 Ni,1-n Results. The test results are shown in Table 2.

[0055] Table 2 Test results of lithium-nickel mixing rate and capacity variation of ternary positive electrode material samples in Example 2

[0056]

[0057] Comparative Example 1

[0058] The commercially available ternary cathode material sample powder to be tested in Example 2 was subjected to XRD test to obtain high-quality full spectrum data. The lithium-nickel mixing ratio was obtained by full spectrum fitting to be 2.571. The test results are shown in Table 3.

[0059] Table 3 XRD test results of the ternary cathode material sample powder in Example 2

[0060] serial number a c V Refinement density Grain size <![CDATA[X Ni ]]> c / a Comparative Example 1 2.8777 14.2386 102.114 4.661 168.185 2.571 4.9479

[0061] From the experimental data in Table 3, it can be seen that the electrochemical measurement method provided by the present invention can better meet the test of evaluating the lithium-nickel mixing rate of the ternary positive electrode material on the lithium battery electrode, and the error range is 1.52% to -4.08% compared with the traditional XRD refinement method.

[0062] Example 3

[0063] Six commercially available ternary cathode materials with known lithium-nickel mixing ratios (measured by XRD full spectrum fitting method) were selected as standard samples. The contents of nickel, cobalt and manganese in these six standard samples were 60wt%, 20wt% and 20wt%, respectively, and were marked as M, M and M. 0-1 、M 0-2 、M 0-3 、M 0-4 、M 0-5 、M 0-6 . The above standard samples, conductive agent Super P and binder PVDF were mixed and slurried in a mass ratio of 9:0.14:0.2, and electrode test pieces were made using general process conditions and assembled into button batteries. The button battery specification is CR2023, the positive electrode is the selected ternary positive electrode material, the negative electrode is a lithium sheet, the separator is a polypropylene film, the electrolyte solvent is a EC / DEC mixed solvent with a volume ratio of 1:1, and the conductive salt is 1M lithium hexafluorophosphate. The packaging pressure of the button battery is 800Pa, and the packaging time is 5 seconds. The reference batteries made from the above ternary positive electrode material standard samples are marked as C 0-1 , C 0-2 , C 0-3 , C 0-4 , C 0-5 , C 0-6 , a total of six sets of tests were carried out.

[0064] The reference battery C 0-1 , C 0-2 , C 0-3 , C 0-4 , C 0-5 , C 0-6The necessary formation and specific capacity tests were performed respectively, and then the battery was pre-charged to a state of charge (SOC) of 100%, at which point the steady-state voltage was controlled at 4.30V vs Li. On a lithium battery electrical performance tester with a potential accuracy of 0.3mV, the discharge phase was measured by combining a constant current discharge CC step with a constant voltage discharge CV step. First, the capacity change in the 4.30V to 3.80V vs Li range was measured. Then continue to discharge to 2.80V vs Li, and record the capacity change in the range of 4.30V to 2.80V vs Li. Among them, the discharge current of the constant current discharge CC step is marked with a multiple, which is set to 0.5C, and the duration of the constant voltage discharge CV step is set to 180min.

[0065] According to the lithium-nickel mixing rate x of the standard sample of the ternary positive electrode material Ni,0-n And the capacity change ratio of the two potential intervals of 4.30V~3.80V vs Li and 4.30V~2.80V vs Li Draw a linear standard curve. The test results are shown in Table 4. The linear standard curve is shown in Figure 2 As shown:

[0066] Table 4 Test results of lithium-nickel mixing rate and capacity variation of standard samples of ternary positive electrode materials in Example 3

[0067]

[0068] Example 4

[0069] A commercially available ternary positive electrode material with an unknown lithium-nickel mixing ratio is selected as the ternary positive electrode material to be tested sample M 1-1 , wherein the contents of nickel, cobalt and manganese are 60wt%, 20wt% and 20wt% respectively, and the battery C to be tested is prepared using the same slurry composition and the same process conditions as in Example 3. 1-1 , and at the same time make parallel test sample battery C 1-2 , C 1-3 , C 1-4 . Place the battery C 1-1 , C 1-2 , C 1-3 , C 1-4 The necessary formation and specific capacity tests were performed respectively, and then the battery was pre-charged to a state of charge (SOC) of 100%, at which time the steady-state voltage was controlled at 4.30 V vs Li. Then, in the discharge stage, the same electrical performance tester and the same test conditions as in Example 1 were used to record the capacity change in the range of 4.30 V to 3.80 V vs Li and 4.30 V to 2.80 V vs Li. and According to the capacity change ratio of the ternary cathode material to be tested in the two potential ranges of 4.30V~3.80V vs Li and 4.30V~2.80V vsLi during the discharge stage Read the lithium-nickel mixing rate x in the standard curve of Example 3 Ni,1-n Results. The test results are shown in Table 5.

[0070] Table 5 Test results of lithium-nickel mixing rate and capacity variation of ternary positive electrode material samples in Example 4

[0071]

[0072] Comparative Example 2

[0073] The commercially available ternary positive electrode material sample powder to be tested in Example 4 was subjected to XRD test to obtain high-quality full spectrum data. The lithium-nickel mixing ratio was obtained by full spectrum fitting to be 2.334. The test results are shown in Table 6.

[0074] Table 6 XRD test results of the ternary positive electrode material sample powder to be tested in Example 4

[0075] serial number a c V Refinement density Grain size <![CDATA[X Ni ]]> c / a Comparative Example 2 2.8756 14.2175 101.816 4.765 167.08 2.334 4.944

[0076] From the experimental data in Table 6, it can be seen that the electrochemical measurement method provided by the present invention can better meet the test of evaluating the lithium-nickel mixing rate of the ternary positive electrode material on the lithium battery electrode, and the error range is 6.38% to -7.67% compared with the traditional XRD refinement method.

[0077] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. An electrochemical measurement method for the lithium-nickel mixing rate of a ternary positive electrode material in a lithium battery electrode, characterized in that: The method comprises selecting at least three ternary positive electrode material standard samples with known lithium-nickel mixing ratios, wherein the main components in the ternary positive electrode material standard samples are the same as the main components in the ternary positive electrode material to be tested samples, preparing the ternary positive electrode material standard samples into reference electrodes by adopting the same process as the lithium battery electrode, assembling the reference electrode and the lithium battery electrode into a battery by the same method, and performing formation and specific capacity tests under the same conditions, and measuring the capacity change q in the potential range of 4.30V to 3.80V in each battery discharge stage. re1 And the capacity change q in the potential range of 4.30V to 2.80V re2 , the lithium-nickel mixing rate x of the standard sample of the ternary cathode material Ni As the ordinate, its capacity change ratio q re2 / q re1 A linear standard curve is established as the horizontal axis, and the lithium-nickel mixing rate of the ternary positive electrode material to be tested in the lithium battery electrode is obtained on the linear standard curve according to the ratio of its capacity change.

2. The electrochemical measurement method of the lithium-nickel mixing rate of the ternary positive electrode material in the lithium battery electrode according to claim 1, characterized in that: The method comprises the following steps: S1: Select at least three lithium-nickel mixing ratios with known values ​​of x Ni,0-n Ternary cathode material standard sample M 0-n , a reference electrode is made by the same process as the lithium battery electrode, and the reference electrode and the lithium battery electrode are assembled into a battery by the same method to obtain a reference battery C 0-n and the battery under test C 1-n ; S2: The reference battery C obtained in step S1 0-n and the battery under test C 1-n Carry out formation and specific capacity tests under the same conditions and record the reference battery C 0-n The capacity change in the discharge phase when the steady-state potential is between 4.30V and 3.80V And the capacity change in the potential range of 4.30V to 2.80V And calculate the capacity change ratio At the same time, record the battery C 1-n The capacity change in the discharge phase when the steady-state potential is between 4.30V and 3.80V And the capacity change in the potential range of 4.30V to 2.80V And calculate the capacity change ratio S3: Using ternary cathode material reference sample M 0-n The mixing rate x Ni,0-n As the ordinate, the capacity change ratio As the abscissa, a linear standard curve was established; S4: Calculate the ternary positive electrode material sample M to be tested according to step S2 1-n Capacity change ratio The ternary cathode material sample M to be tested is calculated according to the linear standard curve in step S3. 1-n The lithium nickel mixing rate x Ni,1-n .

3. The electrochemical measurement method of the lithium-nickel mixing rate of the ternary positive electrode material in the lithium battery electrode according to claim 1 or 2, characterized in that: The number of the standard samples of the ternary positive electrode material is 4 to 6.

4. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 1 or 2, characterized in that: The ternary positive electrode material is a lithium-nickel-cobalt-manganese ternary positive electrode material.

5. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 1 or 2, characterized in that: The lithium-nickel mixing rate of the standard sample of the ternary positive electrode material is measured by using an X-ray diffraction full spectrum fitting method.

6. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 1 or 2, characterized in that: The specific capacity test is completed in the battery discharge stage, and the potential range of the capacity change is determined by setting the steady-state starting potential and the steady-state ending potential; taking the lithium metal electrode potential as the reference zero potential, the steady-state starting potential is 4.30V vs Li, the steady-state ending potentials are 3.80V vs Li and 2.80V vs Li, respectively, and the steady-state potential ranges are 4.30V~3.80V vs Li and 4.30V~2.80V vs Li, respectively.

7. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 6, characterized in that: The control of the steady-state starting potential and / or the steady-state ending potential in the discharge stage is achieved by combining a constant current discharge CC step and a constant voltage discharge CV step.

8. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 7, characterized in that: The current size of the constant current discharge CC step is measured by a multiplier, and the multiplier is 0. <C≤1.0。 9. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 8, characterized in that: The magnification is 0 <C≤0.5。 10. The electrochemical measurement method for the lithium-nickel mixing rate of the ternary positive electrode material in the lithium battery electrode according to claim 7, characterized in that: The termination condition of the constant current discharge CC step is the steady-state starting potential or steady-state ending potential measured by electrochemical measurement.

11. The electrochemical measurement method for the lithium-nickel mixing rate of the ternary positive electrode material in the lithium battery electrode according to claim 7, characterized in that: The potential of the constant voltage discharge CV step is set to a steady-state starting potential or a steady-state ending potential.

12. The electrochemical measurement method of lithium-nickel mixing ratio of ternary positive electrode materials in lithium battery electrodes according to claim 7, characterized in that: The duration of the constant voltage discharge CV step is 10 minutes <t≤180min。 13. The electrochemical measurement method of lithium-nickel mixing rate of ternary positive electrode materials in lithium battery electrodes according to claim 7, characterized in that: The duration of the constant voltage discharge CV step is 60min≤t≤180min.

Citation Information

Patent Citations

  • Synthesis dynamical type ternary material of nanometer fiber, and preparation method thereof

    CN107689451A

  • Method for non-destructively evaluating molar ratio of lithium to cobalt in lithium battery electrode

    CN113740404A